The Effect of Obesity on the Quality of Bowel Preparation for Colonoscopy: Results From a Large Observational Study. Issue 6 (July 2019) - Anklesaria, Ava B.; Ivanina, Elena A.; Chudy-Onwugaje, Kenechukwu O.; Tin, Kevin; Levine, Chaya M.; Homel, Peter; Rojas, Mary; Mayer, Ira E.; Rahmani, Rabin
Abstract : Background: Obesity has been linked to suboptimal bowel preparation but this association has not been conclusively investigated in prospective studies. Goals: Our objective was to determine whether any relationship exists between obesity as measured by body mass index (BMI) and quality of bowel preparation. Study: Adult patients who presented for outpatient colonoscopy at a single urban ambulatory surgery center within a 6-month period and fulfilled inclusion criteria were prospectively enrolled for the study. Patients were divided by BMI into subcategories based on the World Health Organization international classification of obesity. The Modified Aronchick scale was used to assess bowel preparation for colonoscopy. A univariate and multivariate analysis was used to determine a possible association between BMI and poor preparation. Results: A total of 1429 patients were evaluated. On the basis of inclusion criteria, 1314 subjects were analyzed, out of which 73% were overweight or obese. Inadequate bowel preparation was noted in 21.1% of patients. There was no correlation between obesity and the quality of the bowel preparation. Male gender ( P =0.002), diabetes mellitus ( P <0.0001), liver cirrhosis ( P =0.001), coronary artery disease ( P =0.003), refractory constipation ( P <0.0001), and current smoking ( P =0.01) were found to be independently predictive of poor bowel preparation. Conclusions: Increased BMI is not predictive of suboptimal bowel preparation for colonoscopy. The results of our study are pivotal given the increased risk of colorectal cancer in obese patients and their known lower rate of colorectal cancer screening in certain populations. It is important to avoid subjecting these patients to an intensive bowel preparation that may further discourage screening in a patient population that requires it.